TRANSFORMASI FILSAFAT YUNANI KE DUNIA ISLAM DAN KEMUNCULAN FILSAFAT ISLAM - Jon Pamil (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2012)
This article is talking about transformation process of greece’s philosophy to Islam and the appearance of Islamic philosophy. From relevant references, known that the first way of greece’s philosophy transformation to Islam was through translated grecee’s books into Arabic. The emerge of Islamic philosophy influences several factors. The internal factors are: (a) the internal dynamic of Islamic doctrine, (b) the devation of moslem after “khulafa ar-rasyidah”, (c) the conflict between literist and rationalist. While the external factors are: (a) Non Islamic attack to Islamic doctrine by philosopical arguments, (b) literal science and knowledge mixed with philosophy. Besides the factors, there are some pillars of the existing Islamic philosophy such as: (a) An academic translation was existed as Bait al-Hikmah, (b) An organization of scientist was existed in Baghdad at 970 M, called Aljam’iyyah Alsajastaniyah, (c) the existence of secret organization consists of ulama and philosopher named Ikhwan Alshafa.